2009
DOI: 10.1128/jcm.02209-08
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Use of Rectoanal Mucosa-Associated Lymphoid Tissue for Immunohistochemical Diagnosis of Chronic Wasting Disease in White-Tailed Deer ( Odocoileus virginianus )

Abstract: The examination of rectoanal mucosa-associated lymphoid tissue (RAMALT) biopsy specimens for the diagnosis of transmissible spongiform encephalopathies has been described in sheep, elk, and small numbers of mule and white-tailed deer. Previous sample numbers have been too small to validate examination of this type of tissue as a viable antemortem diagnostic test. In this study, we examined RAMALT collected postmortem from 76 white-tailed deer removed from a farm in Wisconsin known to be affected by chronic was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 31 publications
7
31
0
Order By: Relevance
“…9,11 Thus, the pooled estimate of diagnostic test sensitivity of rectal biopsy testing was 68% when based on the 4 herds of the current study, which was refined to 74% (95% CLs: 60% and 85%) after inclusion of data from 2 additional herds from a similarly conducted study (data not shown). 7 Conversely, false-negative results should be expected from rectal biopsy samples in generally one-fourth of all CWD-infected deer. Thus, a negative test result based on a single rectal biopsy sample should not be interpreted as a deer being free of CWD infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9,11 Thus, the pooled estimate of diagnostic test sensitivity of rectal biopsy testing was 68% when based on the 4 herds of the current study, which was refined to 74% (95% CLs: 60% and 85%) after inclusion of data from 2 additional herds from a similarly conducted study (data not shown). 7 Conversely, false-negative results should be expected from rectal biopsy samples in generally one-fourth of all CWD-infected deer. Thus, a negative test result based on a single rectal biopsy sample should not be interpreted as a deer being free of CWD infection.…”
Section: Discussionmentioning
confidence: 99%
“…9 The metaanalytic pooled estimates were first computed using only the herds of the current study (n = 4) and then inclusive of data from 2 additional herds (n = 6 total) from a similarly conducted U.S. study. 7 Unless otherwise stated, all meta-analyses converged with satisfaction of the convergence criterion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations